Sclerospora graminicola Suppresses Plant Defense Responses by Disrupting Chlorophyll Biosynthesis and Photosynthesis in Foxtail Millet - Zhang, Baojun; Liu, Xu; Sun, Yurong; Xu, Lin; Ren, Zhixian; Zhao, Yaofei; Han, Yuanhuai (Frontiers in Plant Science, 2022)
Downy mildew of foxtail millet is an important oomycete disease caused by Sclerospora graminicola, affecting the yield and quality of the crop. Foxtail millet infected with S. graminicola exhibit symptoms of leaf yellowing and leaf cracking. To uncover the pathogenic mechanism of this disease, we explored the effects on chlorophyll synthesis and photosynthesis of foxtail millet leaves infected by S. graminicola. An elite foxtail millet variety, JG21, susceptible to S. graminicola, was used as for this study. S. graminicola inhibited chlorophyll synthesis and caused loose mesophyll cell arrangement. In addition, some cells were severely vacuolated in S. graminicola-infected foxtail millet leaves at the early stages of infection. S. graminicola could invade the mesophyll cells through haustoria which destroyed the chloroplast structure at the middle stages of infection causing significant accumulation of osmiophilic particles (OPs) and disintegrated chloroplast grana lamellae. Furthermore, foxtail millet leaves split longitudinally at the later stages of infection. Chlorophyll and carotenoid contents in infected leaves decreased significantly compared with those in the control. Net photosynthetic rate of leaves decreased continuously, and stomatal conductance and intercellular carbon dioxide concentrations increased significantly following the infection with S. graminicola. A total of 1,618 differentially expressed genes (DEGs) were detected between the control group and the treatment groups using RNA sequencing (RNA-Seq) among S1-S5 stages. DEGs associated with 'photosynthesis' and 'light reaction' were enriched. Gene expression patterns showed that 91.3% of 23 genes related to chlorophyll synthesis and photosynthesis, were significantly down-regulated than the control during S1-S5 stages. Based on the gene expression dataset, related to photosynthesis were screened using WGCNA with 19 gene co-expression modules revealed six hub genes related to chlorophyll synthesis, which were suppressed during infection. The results suggest that infection of S. graminicola lead to weak chlorophyll synthesis and rapid chloroplasts disappearance in foxtail millet. The defense responses and resistance of foxtail millet to S. graminicola were inhibited because chloroplast structure and function were destroyed in leaves, and the sexual reproduction in S. graminicola could be completed rapidly.